Mechanical Thrombectomy for Acute Ischemic Stroke in Patients With Cardiac Myxoma: A Case Series and Pooled Analysis - Rao, Jie; Tao, Zi; Bao, Qiongqiong; Xu, Mengbei; Jiang, Mingxia; Weng, Xiongpeng; Yin, Bo; Li, Dandong; Li, Yan; Cai, Xueli; Fu, Fangwang (Frontiers in Neurology, 2022)
Background and Purpose Acute ischemic stroke (AIS) is a common and life-threatening complication of patients with cardiac myxoma (CM). The role of the mechanical thrombectomy (MT) technique in CM-AIS patients remains unclear, and no guidelines exist for this population. Therefore, we conducted a case series study of MT in CM-AIS patients to investigate its safety and efficacy via a pooled analysis of published literature. Methods Eleven CM-AIS patients who underwent MT between 2016 and 2021 were screened from multicenter stroke databases. Clinical, procedural, and outcome data were obtained from medical records. A systematic review was conducted to identify additional cases from published studies by searching PubMed and China National Knowledge Infrastructure databases. We then performed a pooled analysis of the published cases. Results In the case series study, most patients were male (81.8%), with a median age of 51 years. All patients had CM located in the left atrium. The rate of successful reperfusion using the first-line thrombectomy technique was 100% with stent retriever (SR) and 66.7% with direct aspiration (DA), which resulted in overall successful reperfusion in 94.1% of all occlusions. The retrieved emboli of the five patients who underwent histopathology examination were identified as myxoma components. Hemorrhagic transformation was observed in five (45.5%) patients, of whom one was symptomatic (9.1%). Three-month favorable functional outcomes were achieved in five (45.5%) patients with a 3-month mortality rate of 18.2%. For the literature review, 35 cases with 51 target vessel occlusions were identified and included in the pooled analysis. The rate of successful reperfusion following first-line thrombectomy did not differ between SR (30 patients, 90.9%) and DA (10 patients, 83.3%). The overall successful reperfusion rate was 91.8% of all occlusions. Three-month favorable functional outcomes were achieved in 21 (60.0%) patients, and the mortality rate was 8.6%. Conclusions Our findings suggest that MT is not only an effective technique but also a safe option for CM-AIS patients with large vessel occlusion. MT has several advantages for this population, which include a high recanalization rate, low bleeding risk, and the ability to evaluate the source of emboli and the etiology of stroke.